2020
DOI: 10.1186/s12981-020-00268-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world adherence and persistence for newly-prescribed HIV treatment: single versus multiple tablet regimen comparison among US medicaid beneficiaries

Abstract: Background: Once-daily, single-tablet regimens (STRs) have been associated with improved patient outcomes compared to multi-tablet regimens (MTRs). This study evaluated real world adherence and persistence of HIV antiretroviral therapy (ART), comparing STRs and MTRs.Methods: Adult Medicaid beneficiaries (aged ≥ 18 years) initiating ART with ≥ 2 ART claims during the identification period (January 1, 2015-December 31, 2016) and continuous health plan enrollment for a 12-month baseline period were included. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
(50 reference statements)
6
34
0
1
Order By: Relevance
“… 25 , 28–30 Regardless of the drug formulation, persistence rates remained high 6 months after the index date, corroborating adherence results for treatment-naïve patients rapidly initiated on DRV/c/FTC/TAF in the DIAMOND study, where mean (median) adherence as measured by pill count was 95% (99%) over a 48-week study period. 34 Post-index, a higher proportion of patients achieved PDC≥95% or PDC≥90% with DRV/c/FTC/TAF than with DRV/c+FTC/TAF, consistent with previous literature showing that adherence is higher with STRs than MTRs, 5 , 19–27 , 30 , 35 even when the components of the regimens are the same, as is the case in the current study (2-pill MTR versus STR). Additionally, >50% of patients achieved PDC to any ART ≥95%, higher than the 14–20% who achieved this threshold in a previous study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“… 25 , 28–30 Regardless of the drug formulation, persistence rates remained high 6 months after the index date, corroborating adherence results for treatment-naïve patients rapidly initiated on DRV/c/FTC/TAF in the DIAMOND study, where mean (median) adherence as measured by pill count was 95% (99%) over a 48-week study period. 34 Post-index, a higher proportion of patients achieved PDC≥95% or PDC≥90% with DRV/c/FTC/TAF than with DRV/c+FTC/TAF, consistent with previous literature showing that adherence is higher with STRs than MTRs, 5 , 19–27 , 30 , 35 even when the components of the regimens are the same, as is the case in the current study (2-pill MTR versus STR). Additionally, >50% of patients achieved PDC to any ART ≥95%, higher than the 14–20% who achieved this threshold in a previous study.…”
Section: Discussionsupporting
confidence: 90%
“…The majority of patients used DRV/c/FTC/TAF and had previously received Patients using STR had higher persistence and adherence to the index regimen than those using MTR, consistent with prior studies. 25,[28][29][30] Regardless of the drug formulation, persistence rates remained high 6 months after the index date, corroborating adherence results for treatment-naïve patients rapidly initiated on DRV/c/FTC/ TAF in the DIAMOND study, where mean (median) adherence as measured by pill count was 95% (99%) over a 48-week study period. 34 Post-index, a higher proportion of patients achieved PDC≥95% or PDC≥90% with DRV/c/FTC/TAF than with DRV/c+FTC/TAF, consistent with previous literature showing that adherence is higher with STRs than MTRs, 5,[19][20][21][22][23][24][25][26][27]30,35 even when the components of the regimens are the same, as is the case in the current study (2-pill MTR versus STR).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The US Department of Health and Human Services (DHHS) guidelines for adults and adolescents living with HIV recommend multiple strategies to improve adherence to ART treatments, including providing uninterrupted access to care, motivation for ART initiation, the periodic assessment of adherence to ART and care, patient education on the importance of adherence, and the simplification of ART dosing, such as using a single-table regimen (STR) [ 9 , 10 ]. The use of STRs has been found in several studies to be associated with improved adherence to ART regimens versus multiple tablet regimens (MTRs) among PWH [ 7 , 11 – 15 ] and in some studies was also found to be associated with improved outcomes, including higher levels of viral suppression, decreased hospitalizations, and lower medical costs [ 7 , 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy made it possible to decrease the viral load below the sensitivity limit of diagnostic tests, caused an increase in the level of CD4 lymphocytes, and reduced the incidence of opportunistic infections and the development of full-blown acquired immunodeficiency syndrome (AIDS). As a consequence, mortality in HIV patients has decreased significantly [2][3][4]. However, drug-induced side effects associated with longterm antiretroviral therapy are becoming a growing concern [2,3,5].…”
Section: Introductionmentioning
confidence: 99%